PELATIHAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN ANAK USIA DINI - Sulastri, Ni Made; Herlina, Herlina; Astuti, Farida Herna (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Early Childhood Education is currently only centered on demands for change in the learning process. One of the demands faced by educators in early childhood education institutions is a change in the implementation of the curriculum. Institutions that implement the curriculum still encounter many obstacles and obstacles so that they apply it inconsistently or in accordance with the demands of the curriculum. In developing and improving all the potential and growth aspects of child development, various approaches are needed in learning, one of the approaches that can be applied in early childhood education institutions is the scientific approach, but in reality the scientific learning approach has not been implemented optimally so it is necessary to increase knowledge and competence of educators through workshops and training activities. Through this training it is hoped that scientific learning will be carried out in educational institutions to optimize children's growth and development in an integrated and sustainable manner which in the end can develop intelligent children according to their potential. The implementation of scientific learning activities is carried out in five stages, namely observing, asking, gathering information, reasoning and communicating. The results obtained from this community service activity are increasing the knowledge and abilities of educators in designing scientific learning that can create fun learning activities for students.